2020
DOI: 10.21037/tcr-20-1834
|View full text |Cite
|
Sign up to set email alerts
|

Plantamajoside modulates the proliferation, stemness, and apoptosis of lung carcinoma via restraining p38MAPK and AKT phosphorylation

Abstract: Background Plantamajoside (PMS), an active anti-inflammatory component and antioxidant derived from Herba Plantaginis , has been reported to exert a suppressive effect in liver cancer in vivo . In this study, we tested the effects of PMS on the metastatic 95D cell line. Methods 95D cells were characterized as most sensitive to PMS across several lung cancer cell lines. Cell viability within 24 h was tested with CCK-8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 29 publications
(40 reference statements)
0
7
0
Order By: Relevance
“…This phenomenon is similar to the sacrificial reagent role in the photocatalytic H 2 evolution reaction, such as a TiO 2 semiconductor as a methanol sacrificial reagent 47,48 and a g-C 3 N 4 photocatalyst as a TEOA sacrificial reagent. [49][50][51] Ethanol was oxidized to acetaldehyde during the reaction. During the photocatalytic reaction, photogenerated holes migrate to the liquid-solid interface (Ni/NiS-ZCS and ethanol) to activate ethanol and deprotonate for generating protons (H + ).…”
Section: Catalysis Science and Technology Papermentioning
confidence: 99%
“…This phenomenon is similar to the sacrificial reagent role in the photocatalytic H 2 evolution reaction, such as a TiO 2 semiconductor as a methanol sacrificial reagent 47,48 and a g-C 3 N 4 photocatalyst as a TEOA sacrificial reagent. [49][50][51] Ethanol was oxidized to acetaldehyde during the reaction. During the photocatalytic reaction, photogenerated holes migrate to the liquid-solid interface (Ni/NiS-ZCS and ethanol) to activate ethanol and deprotonate for generating protons (H + ).…”
Section: Catalysis Science and Technology Papermentioning
confidence: 99%
“…apoptosis in lung cancer via dephosphorylation of MAPK and AKT, as well as mitochondria dysfunction. 127…”
Section: Regulation Of Oxidative Stress and The Antioxidant Balancementioning
confidence: 99%
“…The apigenin ( 1 ) and luteolin ( 2 ) down-regulate NF-κB signaling (IKK, IκB, and NF-κB) and PI3K/AKT signaling (PI3K, AKT, and mTOR); activate or inactivate various signaling targets, such as Bcl-2, Bcl-xL, Bax, caspase-3, and caspase-9; and promote mitochondrial-mediated apoptosis, thereby producing anticancer effects. Strangely, apigenin ( 1 ) can stimulate autophagic cell apoptosis of gastric cancer via inhibition of HIF-1α and Ezh2 under hypoxia conditions . Acteoside ( 27 ) increases the expression of Bax, caspase-3, and caspase-9 and reduces the expression of Bcl-2, cleaved caspase-3, and cleaved caspase-9 to promote tumor cell apoptosis. In addition, plantamajoside ( 25 ) initiates cell apoptosis in lung cancer via dephosphorylation of MAPK and AKT, as well as mitochondria dysfunction …”
Section: Biological Activities and Molecular Pharmacologymentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that PMS has a wide range of biological activities. , A recent study showed that PMS ameliorated lipopolysaccharide-induced acute lung injury by inhibiting NF-κB as well as MAPK activation. , In addition, PMS can inhibit histone deacetylase 2 (HDAC2) activity in vitro and in vivo and attenuate isoproterene-induced cardiac hypertrophy . HDAC2 is an enzyme that removes acetyl groups from lysine residues at the amino-terminal tail of histones . HDAC2 is upregulated in SN microglia in PD and prevents MPTP-induced loss of SN dopaminergic neurons by inhibiting the inactivation of the MAPK pathway induced by HDAC2 .…”
Section: Introductionmentioning
confidence: 99%